From exclusive health and climatic resorts to affordable summer holidays: ENIT’s seaside tourism promotion in English over the years (Altre Modernità, 2025)
This paper traces the evolution of seaside tourism from early forms of bathing and thermal tourism through an analysis of ENIT’s English promotional production. With the goal of understanding the factors behind the spread and success of mass seaside and coastal tourism in specific Italian regions, the paper discusses how the concept of balneotherapy became intertwined with different kinds of leisure and entertainment activities throughout the 20th century. This research specifically explores if and how changing sociocultural trends and the needs of foreign tourists were reflected in ENIT’s publications, advancing hypotheses on the institution’s role in shaping and reproducing narratives related to the consumption and appreciation of water and marine environments. The categorisation and analysis of ENIT’s brochures and magazines and their publication trends allowed to identify the geographical areas and types of thermal and coastal tours promoted over time. A qualitative investigation of key terminology contributed to an understanding of varying connotations depending on the time period and geographical region. The results are crucial to understanding the historical, socio-economic shift that preceded and informed the mass promotion and commodification of seaside tourism, from the 1930s onwards, as a regenerating and widely accessible holiday opportunity and as one of the root causes of unsustainable forms of contemporary tourism.
Keywords: Italian Government Tourist Board; bathing tourism; seaside tourism; mass consumption; diachronic analysis